2017
DOI: 10.1111/acem.13076
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the DHAKA Score for Diagnosing Severe Dehydration in Children with Acute Diarrhea in Resource‐limited Settings

Abstract: BackgroundAcute diarrhea remains both common and deadly in children worldwide. Proper treatment depends on accurately assessing dehydration status. Current World Health Organization (WHO) guidelines include an algorithm for classifying children as having no, some, or severe dehydration, which has never been properly validated. The Dehydration: Assessing Kids Accurately (DHAKA) study recently derived a new scoring system for dehydration in children, but it requires external validation.MethodsOur study enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The DHAKA score was the first empirically derived and externally validated model for assessing dehydration in children with acute diarrhea in a lowresource setting. 9,16 The score was designed to be used by nurses in resource-limited settings to quickly determine a child's degree of dehydration based on clinical signs and symptoms and was shown to be both more accurate and reliable than the Integration Management of Childhood Illness algorithm in a limited-resource setting. 9 Recent research has also shown the promise of sonographic measurements as a predictor of diarrheal dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The DHAKA score was the first empirically derived and externally validated model for assessing dehydration in children with acute diarrhea in a lowresource setting. 9,16 The score was designed to be used by nurses in resource-limited settings to quickly determine a child's degree of dehydration based on clinical signs and symptoms and was shown to be both more accurate and reliable than the Integration Management of Childhood Illness algorithm in a limited-resource setting. 9 Recent research has also shown the promise of sonographic measurements as a predictor of diarrheal dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…9 The DHAKA score, which uses a combination of several signs and symptoms, was the first clinical diagnostic tool for assessing dehydration to be externally validated in a resource-limited setting, where it outperformed the WHO algorithm. 9 In addition to clinical symptoms, recent research has identified sonographic measurement of the ratio of aorta-to-inferior vena cava diameter (Ao/IVC) to be a moderately accurate assessor of dehydration in children. [10][11][12][13] The DHAKA study also looked at sonographic measurement of the Ao/IVC ratio as a predictor of dehydration.…”
mentioning
confidence: 99%
See 3 more Smart Citations